Studi Kelayakan Investasi Proyek Kopi â€ZOAâ€ di Jakarta Selatan - Utami, Adita; Ghaneswari, Kadek Wulan; Mentari, Larasati Mega (Universitas Dr. Soetomo, 2021)
The economy is progressing at this time starting from the number of small-medium businesses, especially businesses in the culinary field, one of which is a coffee shop. Drinking coffee has become a lifestyle so this makes a high demand, then becomes a business opportunity to open a coffee shop. Moreover, starting a coffee shop business is not that difficult. However, studies still need to be done so that the business can run smoothly and earn profits. This study will discuss whether a coffee shop business, in this study is Zoa Coffee Shop is economically feasible to run. Therefore, to find out whether a business is feasible, a feasibility study is needed. In the feasibility study discusses aspects of the feasibility study such as market aspects, technical aspects and management aspects. In addition, this research will discuss the investment feasibility analysis using the Net Present Value (NPV) method and also sensitivity analysis. From the results of the analysis and calculation, Zoa Coffee Shop meets the eligibility requirements to start. The NPV value of the study results is positive. The value of the Sensitivity Analysis by assuming some cost increases, the NPV value is still positive, indicating that the Zoa coffee business is still feasible.